Topical capsaicin 0,075% versus menthol 1% efficacy and safety in HIV-associated eosinofilic folliculitis - Galarza, Carlos (2007)
Objetive: To determine efficacy and safety of capsaicin 0,075% topical therapy in the treatment of pruritus due to eosinophilic folliculitis in HIV patients with lymphocyte count CD4 (+) <250 x mm3. Design: Randomized clinical trial, double blind study. Setting: Infectious and Tropical Diseases Service and Dermatology Service, Hospital Nacional Dos de Mayo, Lima, Peru. Participants: Patients with VIH-associated eosinophilic folliculitis. Interventions: Forty patients with HIV-associated eosinophilic folliculitis were randomly distributed in two groups: group 1 included 20 patients that received sample 1 and group 2, 20 patients that received sample 2. Patients received capsaicin 0,075% and menthol 1% treatments (marked as sample 1 and sample 2). Instructions on topical use each 6 hours were given to patients. Visits were programmed to evaluate efficacy and monitor adverse events by study drugs. Main outcome measures: Capsaicin and menthol administration clinical outcome. Results: We found good response in 90% of patients receiving capsaicin 0,075% (18/20) versus 40% of the group treated with menthol 1% (88/20), with significant statistical difference (p= 0,001), OR = 0,074% (IC 95%: 0,013 – 0,411). Topical therapy efficacy was altered by CD4 lymphocyte count (p< 0,001); otherwise the occurrence of opportunistic diseases (p= 0,252) did not affect therapy efficacy. There were local adverse events (erithema and heat) in 3 patients (15%) who received capsaicin 0,075% and only in one patient (5%) of group 2 (menthol) who presented erithema (5%), with no significant statistical difference (p> 0,05). Conclusions: Capsaicin topical therapy is effective and safe in the treatment of pruritus in HIV-associated eosinophilic folliculitis.